Is forest bathing a panacea for mental health problems? A narrative review - Chen, Hongxia; Meng, Zhongji; Luo, Jie (Frontiers in Public Health, 2025)
BackgroundThe fast pace of modem life brings great pressure, which lead to physical and mental health issues. Researches have demonstrated that forest bathing can considerably alleviate symptoms of depression and anxiety, eliminate negative emotions and promote mental wellbeing. We presented evidences of the positive impact of forest bathing on mental health in the context rapid urbanization and surging health needs in the post-pandemic era, and outlined the current insights into the related factors affecting the effect of forest bathing, as to provide directions for future interventions or research.MethodThe electronic databases PubMed, Cochrane Library, Embase, Web of Science Core Collections and the China Academic Journals (CAJ) offered through the Full-text Database (CNKI) were searched for relevant studies published from the inception of the databases to December 2024. The initial search strategy was performed using keywords, MeSH terms, and free text words such as “forest bathing”, “forest medicine”, “mental health pressure”, “anxiety”, “depression”, “cortisol”, etc.ResultsThe synthesis of the findings in the included studies revealed that forest bathing interventions might improve mental and physical health, reduce blood pressure, improve sleep quality and boost immunity, as well as alleviate depression, anxiety, and stress. Furthermore, the effect of forest bathing on mental health indicators and the differences in these results among different populations varied. Forest environment, tree species, exposure duration, season, composition and concentration of volatile organic compounds have an impact on the effect of forest bathing.ConclusionsForest bathing were effective in lowering cortisol levels, reducing sympathetic nerve activity, as well as improving negative mood, which could serve as a non-pharmacological treatment for mental health in the general population.